First description and validation of a new method for estimating aortic stenosis burden and predicting the functional response to TAVI - de la Torre Hernandez, Jose M.; Veiga Fernandez, Gabriela; Ben-Assa, Eyal; Iribarren, Julia; Sainz Laso, Fermin; Lee, Dae-Hyun; Ruisanchez Villar, Cristina; Lerena, Piedad; Garcia Camarero, Tamara; Iribarren Sarrias, Jose L.; Cuesta Cosgaya, Jose M.; Maza Fernandez, Maria E.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Up to one-fifth of patients continue to have poor quality of life after TAVI, with an additional similar proportion not surviving 1 year after the procedure. We sought to assess the value of a new method based on the integrated analysis of left ventricular outflow tract flow velocity and aortic pressure to predict objective functional improvement and prognosis after TAVI.In a cohort of consecutive patients undergoing TAVI flow velocity-pressure integrated analysis was obtained from simultaneous pressure recordings in ascending aorta and flow velocity recordings in left ventricular outflow tract by echocardiography. Objective functional improvement at 6 months after TAVI was assessed through changes in 6minute walk test and NT-proBNP levels. Clinical follow-up was conducted at 2 years.Of the 102 patients studied, 82 (80.4%) showed objective functional improvement. The 2-year mortality of these patients was significantly lower (9% vs. 44%, p=0.001). In multivariate analysis the parameter, "(Pressure at Vmax -Pressure at Vo) / Vmax", resulted independent predictor for objective improvement. The C-statistic was 0.70 in overall population and 0.78 in low-gradient subgroup. All echocardiographic parameters and the valvulo-arterial impedance showed C-statistic <0.6 for overall and low-gradient patients. In a validation cohort of 119 patients, the C-statistic was 0.67 for the total cohort and 0.76 for the low-gradient subgroup.This new method allows predicting objective functional improvement after TAVI more precisely than the conventional parameters used to assess the severity of aortic stenosis, particularly in patients with low-gradient.